2015
DOI: 10.1586/1744666x.2015.1037287
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and diagnosis of adult-onset Still’s disease: the implications of current and emerging markers in overcoming the diagnostic challenge

Abstract: Adult-onset Still's disease (AOSD) is a known cause of fever of unknown origin. It is characterized by a triad of symptoms: spiking fever (>39°C), salmon-colored rash and arthritis/arthralgia. On a predisposing genetic background, several conditions may act as trigger for disease and among these, infectious agents are the most important. Nowadays, a dichotomous view of AOSD has been introduced which distinguishes this entity in two subsets according to the clinical features and laboratory aspects: systemic or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 106 publications
(102 reference statements)
2
27
0
5
Order By: Relevance
“…PCT levels can be useful not only for distinguishing between GNB and GPB infections, but also between GNB or GPB bacterial species. [4,9,13,16,19,20] 12 0.21 (0.07-2.03) Soft tissue infection [5,10,14,17,19,21] 12 0.82 (0.18-7.13) Pelvic infection [6,11,15,18,20,21] Thus, PCT levels are a marker for sepsis, which can inform decisions on the ideal antimicrobial treatment for patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCT levels can be useful not only for distinguishing between GNB and GPB infections, but also between GNB or GPB bacterial species. [4,9,13,16,19,20] 12 0.21 (0.07-2.03) Soft tissue infection [5,10,14,17,19,21] 12 0.82 (0.18-7.13) Pelvic infection [6,11,15,18,20,21] Thus, PCT levels are a marker for sepsis, which can inform decisions on the ideal antimicrobial treatment for patients.…”
Section: Resultsmentioning
confidence: 99%
“…An episode was defined as the time period associated with one or more positive BCs for the same organism(s) [12,13]. PCT levels may be altered in some non-infectious diseases, such as autoimmune disease [14][15][16][17][18] and malignant tumors [19][20][21]. Therefore, our exclusion criteria were: (1) a medical history of immune system disease (adult-onset Still's disease, rheumatoid arthritis, ankylosing spondylitis, systemic lupus erythematosus, vasculitis, or multiple sclerosis) [14][15][16][17][18]; and (2) history of malignant tumor (thyroid carcinoma or lung cancer) [19][20][21].…”
Section: Patients and Samplesmentioning
confidence: 99%
“…Subsequent phosphorylation of several kinases leads to translocation of NF-κB to the nucleus and final expression of a large portfolio of inflammatory genes (Weber et al, 2010). The IL-1 family comprises 11 members (Dinarello, 2011), and some investigators (Colafrancesco et al, 2012; Priori et al, 2014) have shown that IL-1α/β and IL-18 are crucial in the pathogenesis of AOSD and are valid serological biomarkers of the disease (Colafrancesco et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Ezzel egyidőben a szérum ferritin egy izotípusának a glikozilált ferritinnek (GF) a szintje csökken . Egészséges egyénekben a GF a szérum ferritin 50-80%-t teszi ki, míg a betegség akut szaka alatt 20%-ra csökken, és a remissziók alatt a szérum ferritin szinttel ellentétben nem normalizálódik [10,15,16] . E két érték együttes vizsgálata tovább növeli a diagnosztika szenzitivitását [4,5] .…”
Section: Esetismertetésunclassified
“…A szérum IL-18, prokalcitonin, S-100, szérum CD163 markerek szerepe és a diagnosztikus haszna még további vizsgálatokat igényel [15,16] .…”
Section: Esetismertetésunclassified